Differences between the Canadian military's Regular and Reserve Forces in perceived need for care, mental health services use and perceived sufficiency of care: a cross-sectional survey. Issue 9 (18th September 2019) - Boulos, David; Fikretoglu, Deniz
Abstract : Objective: The primary objective was to explore differences in perceived need for care (PNC), mental health services use (MHSU) and perceived sufficiency of care (PSC) between Canadian Armed Forces Regular Force (RegF) and Reserve Force (ResF) personnel with an objective need for mental health services. Design: Data came from the 2013 Canadian Armed Forces Mental Health Survey, a cross-sectional survey of serving personnel (n=72 629). Analyses were among those with an Afghanistan deployment and an identified mental disorder (population n=6160; sampled n=868). Logistic regression compared PNC, MHSU and PSC between RegF and ResF. Covariate-adjusted marginal prevalence difference estimates were computed. Primary outcome measure: The primary outcomes were PNC, MHSU and PSC. Each had three service categories, including an aggregate 'any' of the three: (1) information about problems, treatments or services; (2) medication and (3) counselling. Results: ResF had an 10.5% (95% CI −16.7% to −4.4%) lower perceived need for medication services but PNC differences were not significant for other service categories. MHSU tended to be lower for ResF; 9.1% (95%CI −15.5% to −2.6%) lower for medication, 5.4% (95% CI −11.5% to 0.7%) lower, with marginal significance, for counselling and 11.3% (95% CI −17.3% to −5.2%) lower for the 'any' service category. Additionally, ResF tended to have a lower fully met need for care; 13.4% (95% CI −22.1% to −4.6%) lower for information, 15.3% (95% CI −22.9% to −7.6%) lower for counselling and 14.6% (95% CI −22.4% to −6.8%) lower for the 'any' service category. Conclusions: Our findings suggest MHSU and PSC differences between Canadian RegF and ResF personnel that are not fully accounted for by PNC differences. Deficits in ResF members' perceptions of the sufficiency of information services and counselling services suggest perceived, or experienced, barriers to care beyond any PNC barriers. Additional research assessing barriers to mental healthcare is warranted.